Analisis Efektivitas Perusahaan Perspektif Ekonomi Islam (Studi Multi Kasus Pada Perusahaan Pengolahan Udang di Provinsi Jawa Tengah) - Sari, Rizka Farikha; Raharjo, Susilo Toto (ITB AAS INDONESIA Surakarta, 2024)
Dhoopar introduced an integrated conceptual model of organizational effectiveness (OE) that considers the levels of antecedents (individual, group, and organizational) as well as measures of (financial, operational, structural, and attitudinal). This research aims to analyze company effectiveness using that model through a multi-case study of shrimp processing companies in Central Java Province. This research uses a qualitative methodology. The findings of this study can help decision makers and stakeholders in adopting, designing and implementing proactive internal control systems to improve operational efficiency, effectiveness and competitive advantage. Because this research concentrates on fish processing companies that have different characteristics, the generalizability of the conclusions may be limited.